2012
DOI: 10.1128/jvi.06892-11
|View full text |Cite
|
Sign up to set email alerts
|

Temporal- and Strain-Specific Host MicroRNA Molecular Signatures Associated with Swine-Origin H1N1 and Avian-Origin H7N7 Influenza A Virus Infection

Abstract: MicroRNAs (miRNAs) repress the expression levels of genes by binding to mRNA transcripts, acting as master regulators of cellular processes. Differential expression of miRNAs has been linked to virus-associated diseases involving members of the Hepacivirus , Herpesvirus , and Retrovirus families. In contrast, limited biological and molecular information has been reported on the potential role of cellular miRNAs in the life cycle of influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 64 publications
3
93
4
1
Order By: Relevance
“…In addition, temporal-and strain-specific miRNA expression was profiled in A549 cells infected with either pandemic H1N1 (2009) or H7N7 (2003), but these studies lacked the pressure normally exerted by the host immune system (28). Consequently, longitudinal changes in miRNA expression and their targets during influenza infection and how they relate to viral replication and host response in vivo remain poorly understood.…”
mentioning
confidence: 99%
“…In addition, temporal-and strain-specific miRNA expression was profiled in A549 cells infected with either pandemic H1N1 (2009) or H7N7 (2003), but these studies lacked the pressure normally exerted by the host immune system (28). Consequently, longitudinal changes in miRNA expression and their targets during influenza infection and how they relate to viral replication and host response in vivo remain poorly understood.…”
mentioning
confidence: 99%
“…Influenza A virus infection involves many host factors including miRNAs Loveday et al, 2012). It has been reported that influenza A virus infection causes changes in the profile of host miRNAs.…”
Section: Identification Of Mirnas Suppressing Influenza a Virus Replimentioning
confidence: 99%
“…Microarray analysis of mouse miRNA expression during infection with the reconstructed 1918 pandemic influenza virus and a seasonal H1N1 virus (Tx/91) established that the miRNAome was modulated during infA infection (Li et al, 2010). In our previous study, we profiled human miRNA expression during infection with the low-pathogenicity (LP) swine-origin 2009 pandemic H1N1 infA and the highly pathogenic (HP) avian-origin H7N7 infA (Loveday et al, 2012). Our studies demonstrated temporal and strain-specific regulation of miRNAs during infA infection, especially for the HP H7N7 virus.…”
Section: Introductionmentioning
confidence: 99%